Living positive experiences in store: how it influences shopping experience value and satisfaction? - Cachero-Martínez, Silvia; Vázquez-Casielles, Rodolfo (Journal of Business Economics and Management, 2017)
Retailers have tried to differentiate themselves from their competitors through shopping experience. This is the first study analysing relationships between experience dimensions, shopping experience value and satisfaction. In this article different shopping experience dimensions are identified: emotional, sensory, intellectual, social, and pragmatic. In-depth interviews were conducted with a panel of experts to adapt a set of experience dimensions identified from the literature to the offline environment. A survey was then designed to collect data from consumers who had bought in a retailer, where marketing strategies are linked with experience dimensions. Retailers may use this typology in order to re-design their marketing strategies. Retailers must invest in utilitarian attributes of product assortment offered to consumers, improving quality while maintaining prices and promotions. If a retailer can stimulate social shopping and consumer curiosity, such as imagination and creativity in the store, they will have more devoted consumers.